The effect of bilayer graphene on sensitivity of surface plasmon resonounce biosensor - Tousi, Hamid Toloue Ajili (2015)
In this paper, the effect of bilayer graphene on sensitivity of surface plasmon resonance (SPR) biosensor is numerically presented. It shows that the zero reflection at the resonance angle occurred by choosing proper thickness for gold and graphene layers. This research analyzes light reflection in angular modulation with a fixed wavelength (?=633 nm) of incident light regarding to variation in thickness of gold layer underlying bilayer graphene. In comparison to the conventional SPR sensors, graphene based sensor gives a larger local change in the refractive index near the sensor surface. The light reflection coupled into a SPR mode propagating along a gold-graphene layer is calculated and compared to a conventional SPR sensor with varied gold thicknesses.